THE SUPPLY CHAIN OF FRESH TEA LEAVES FROM SMALLHOLDER FARMERS IN BANDUNG REGENCY - Sotya T. Anggita; Fadil Bagaskara; Kralawi Sita; Yayan Herdiana (Gunung Djati Conference Series, 2026)
This study aims to map the structure, distribution flow, and dynamics of the smallholder tea shoot supply chain in Bandung Regency, Indonesia, with a focus on industrial absorption capacity, supply gaps, and strengthening upstream–downstream partnerships. The research employed a survey approach involving smallholder tea farmers and tea processing factories receiving fresh tea leaves, complemented by a descriptive supply chain analysis. The supply chain is characterized by farmers as the primary producers, who generally market fresh tea leaves through multiple layers of collectors (Collector 1 to Collector 3) before reaching processing factories. The receiving factories comprise smallholder-owned tea factories, private tea factories, and factories managed by the Indonesia Research Institute for Tea and Cinchona (IRITC), with smallholder tea factories operated either by Village Unit Cooperatives or individual owners. In several cases, the supply chain has begun to exhibit a disintermediation pattern, whereby farmers or farmer groups deliver fresh tea leaves directly to processing factories. The study identified at least 11 factories receiving smallholder tea leaves, with a combined processing capacity of approximately 75–100 tons of fresh tea leaves per day, whereas the current production reaches only 45–50 tons per day, resulting in a substantial supply gap. This condition reflects suboptimal productivity, inconsistent tea shoot quality, and weak price incentives at the farm level. In addition, an alternative supply chain serving premium markets, such as cafés and tea houses, has emerged, although its scale remains limited. Strengthening upstream–downstream partnerships is essential to improve coordination, ensure product traceability, enhance quality, and promote price transparency and stability. The required strategies include increasing production through crop intensification and replanting, improving harvesting and postharvest practices, strengthening farmer organizations, and diversifying market channels to enhance value addition and ensure the long-term sustainability of the smallholder tea supply chain.